Effects of Two High-intensity Interval Training Concepts in Recreational Runners - Faelli, Emanuela; Ferrando, Vittoria; Bisio, Ambra; Ferrando, Mara; Torre, Antonio La; Panasci, Marco; Ruggeri, Piero (International Journal of Sports Medicine, 2019)
This study investigated the effects induced by 8 weeks of two high-intensity interval training (HIIT) protocols, 10–20–30 and 30–30 concepts, characterized by significantly different training volume and intensity, on physiological parameters, running performance, body composition and psychophysiological stress of recreational divided into two groups: the 10–20–30 group performed two 10–20–30 sessions/wk and one continuous training (CT)/wk, whilst the 30–30 group performed two 30–30 sessions/wk and one CT session/wk. VO2max, 1 km time, maximal aerobic speed (MAS), and body composition were evaluated before and after intervention. Internal load was measured through rating of perceived exertion (RPE). Both groups significantly improved running performance (1 km time: p=0.04; MAS: p=0.000001), aerobic fitness (VO2max: p=0.000002) and body composition (lean mass (kg) p=0.0001; fat mass (%) p=0.00005). RPE resulted significantly lower in the 10–20–30 group than in 30–30 group (10–20–30: 13.36±0.28; 30–30:15.55±0.21; p=0.0002). Thus, the 10–20–30 group improved physiological parameters, performance and body composition, similar to 30–30 with significantly lower RPE values. These results suggest that in recreational runners the 10–20–30 training is effective in improving aerobic fitness and performance, with a lower subjective perception of effort, thus enhancing individual compliance and adherence to the prescribed training program.
Keywords: 10–20–30 training; 30–30 training; body composition; rating of perceived exertion